Possible role of vitamins C and E co-administration in the prevention of testicular ischemia–reperfusion injury following surgical repair of torsion of the testis - Ogunleye, Olajumoke Deborah; Afolabi, Oladele Ayobami; Saka, Waidi Adeoye; Olusola, Bamidele Oluwole; Ajike, Richard Adedamola; Oladokun, Olayemi Olutobi; Hammed, Sodiq Opeyemi; Hezekiah, Oluwaseun Samuel; Adedeji, Oreoluwa Janet (Frontiers in Nutrition, 2025)
Torsion of the testis (TT) is a recognised urological emergency whereby twisting of the spermatic cord causes testicular ischemia. Surgical detorsion restores perfusion, but inevitably results in testicular ischemia–reperfusion injury (tIRI). The resultant of this is oxidative stress, inflammation, impaired steroidogenesis, and a loss of spermatogenic function. Although single-agent antioxidants have been evaluated by previous studies in the mitigation of tIRI, there is limited evidence that addresses the additive or synergistic protection of co-administration of vitamins C and E after detorsion. Mechanistic data indicate possible complementary actions of vitamin E’s (α-tocopherol) protection of membrane lipids from peroxidation and vitamin C’s (ascorbate) clearance of aqueous reactive oxygen species, which regenerates oxidized α-tocopherol back to its active form. Together, they reduce lipid peroxidation markers, attenuate neutrophil-mediated oxidative bursts, suppress NF-κB-driven pro-inflammatory signalling, and may activate cytoprotective pathways such as Nrf2/HO-1. Preclinical studies show more consistent reductions in oxidative damage and inflammatory markers with combined treatment than with either vitamin alone. However, most evidence derives from animal and in vitro models. Hence, heterogeneity in dosing, timing (pre- vs. post-treatment), and outcome measures limits direct clinical translation. This review, therefore, examines preclinical and mechanistic studies of vitamins C and E co-administration in models of tIRI and related ischemic injuries.